Development of Professionalism in Graduate Medical Education: A Case-Based Educational Approach From the College of American Pathologists' Graduate Medical Education Committee. (26th June 2018) - Conran, Richard M.; Powell, Suzanne Zein-Eldin; Domen, Ronald E.; McCloskey, Cindy B.; Brissette, Mark D.; Cohen, David A.; Dixon, Lisa Ross; George, Melissa Robin; Gratzinger, Dita A.; Post, Miriam D.; Roberts, Cory A.; Rojiani, Amyn M.; et al.
Professionalism and physician well-being are important topics in academic medicine. Lapses in professional judgment may lead to disciplinary action and put patient's health at risk. Within medical education, students and trainees are exposed to professionalism in the institution's formal curriculum and hidden curriculum. Development of professionalism starts early in medical school. Trainees entering graduate medical education already have developed professional behavior. As a learned behavior, development of professional behavior is modifiable. In addition to role modeling by faculty, other modalities are needed. Use of case vignettes based on real-life issues encountered in trainee and faculty behavior can serve as a basis for continued development of professionalism in trainees. Based on the experience of program directors and pathology educators, case vignettes were developed in the domains of service, research, and education and subdivided into the areas of duty, integrity, and respect. General and specific questions pertaining to each case were generated to reinforce model behavior and overcome professionalism issues encountered in the hidden curriculum. To address physician burnout, cases were generated to provide trainees with the skills to deal with burnout and promote well-being.